2017
DOI: 10.1097/sla.0000000000001645
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported Limitations to Surgical Buy-in

Abstract: Objective To characterize how patients buy-in to treatments beyond the operating room and what limits they would place on additional life-supporting treatments. Background During a high-risk operation, surgeons generally assume that patients buy-in to life-supporting interventions that might be necessary postoperatively. How patients understand this agreement and their willingness to participate in additional treatment is unknown. Methods We purposively sampled surgeons in Toronto, Ontario, Boston, Massach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Patients trust their surgeon to make treatment decisions on their behalf yet often have strong preferences about prolonged life-sustaining treatments . This discrepancy can cause conflict among clinicians, patients, and families .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients trust their surgeon to make treatment decisions on their behalf yet often have strong preferences about prolonged life-sustaining treatments . This discrepancy can cause conflict among clinicians, patients, and families .…”
Section: Introductionmentioning
confidence: 99%
“…atients trust their surgeon to make treatment decisions on their behalf yet often have strong preferences about prolonged life-sustaining treatments. 1 This discrepancy can cause conflict among clinicians, patients, and families. 2,3 Routine preoperative discussion of preferences for life-sustaining treatments allows patients to discuss and document the care they would not want if they became too sick to speak for themselves.…”
mentioning
confidence: 99%
“…As both a bowel obstruction and septic shock secondary to Clostridium difficile infection are indications for surgery (25,26), the relative reluctance to consult surgery may indicate an assumption by residents that the scope of a DNR/DNI order may contraindicate endotracheal intubation for general anesthesia or an assumption that DNR/DNI patients would prefer not to receive aggressive interventions such as surgery. This assumption may not always be valid: a recent qualitative study found that several patients who expressed a desire to avoid CPR in the event of cardiac arrest would nonetheless accept high-risk surgical procedures (27).…”
Section: Discussionmentioning
confidence: 99%
“…30 Of the literature on shared decision making for surgery, only a small number of North American studies focus on high-risk patients. [31][32][33][34] Two have focused on how surgeons and patients discuss options in the event that postoperative complications are severe or life threatening. Analysis of audio recorded shared decision making encounters for high-risk surgery identified significant communication gaps regarding potentially severe postoperative complications.…”
Section: Open Accessmentioning
confidence: 99%